Food colloids fundamentals of formulation - Dickinson, Eric; Miller, Reinhard (Royal Society of Chemistry, 2001)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. Food Colloids: Fundamentals of Formulation describes the physico-chemical principles underlying the formulation of multi-component, multi-phase food systems. Emphasis is placed on the interfacial properties of proteins and the role of protein interactions in determining the properties of emulsions, dispersions, gels and foams. The coverage includes authoritative overviews of conceptual issues as well as descriptions of new experimental techniques and recent food colloids research findings. Specific topics include atomic force microscopy, aggregation phenomena, coalescence mechanisms, crystallization processes, surface rheology, protein-lipid interactions and mixed biopolymer systems. This book provides essential new material for those active in the field and is suitable for postgraduates and researchers, both in industry and academia.
"Proceedings of the conference Food colloids 2000: fundamentals of formulation organized by the Food Chemistry Group of the RSC held on 3-6 April 2000 in Potsdam, Germany."-T.p. verso.
Keywords: Colloids -- Congresses.; Food -- Composition -- Congresses.; elektronické knihy; electronic books